2016
DOI: 10.1007/s00442-016-3599-0
|View full text |Cite
|
Sign up to set email alerts
|

Investment in boney defensive traits alters organismal stoichiometry and excretion in fish

Abstract: Understanding how trait diversification alters ecosystem processes is an important goal for ecological and evolutionary studies. Ecological stoichiometry provides a framework for predicting how traits affect ecosystem function. The growth rate hypothesis of ecological stoichiometry links growth and phosphorus (P) body composition in taxa where nucleic acids are a significant pool of body P. In vertebrates, however, most of the P is bound within bone, and organisms with boney structures can vary in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 71 publications
4
66
1
1
Order By: Relevance
“…Previous studies have shown that investment in bony structures can increase phosphorus demand, which can potentially alter how fish forage and recycle nutrients (El‐Sabaawi et al ., ; Durston & El‐Sabaawi, ; Leal et al ., ). We find that, despite dramatic environmental fluctuations, the expected association between %P and armor remains strong.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that investment in bony structures can increase phosphorus demand, which can potentially alter how fish forage and recycle nutrients (El‐Sabaawi et al ., ; Durston & El‐Sabaawi, ; Leal et al ., ). We find that, despite dramatic environmental fluctuations, the expected association between %P and armor remains strong.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, lateral plates and Eda vary dramatically within and among the estuaries, generating the high levels of variation in %P. This variation should have a major influence on whole fish elemental ratios and thus the observed variation in %P is likely to influence the balance between excretion rates and diet choice (El‐Sabaawi et al ., ; Durston & El‐Sabaawi, ). Given that allelic variation at Eda appears to be driving variation in elemental composition, and because Eda is generally subject to strong natural selection in the wild (Colosimo et al ., , ; Barrett et al ., ; Jones et al ., ), it is likely that elemental composition in %P can evolve just as rapidly as can lateral plates (see Durston & El‐Sabaawi, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking TBE with ES therefore enables us to make predictions regarding the impact of human activities on both community structure and functioning. For example, it has been observed that communities dominated by species with higher optimal N:P ratios will substantially influence biogeochemical cycles by preferentially recycling N over P Knoll et al, 2009;El-Sabaawi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we failed to detect the environmental pressures driving divergences in these two traits. The variability in excretion rate probably stands in trophic and stoichiometric factors, such as trophic niche, elemental composition of resources, or allochthonous nutrient inputs (El‐Sabaawi, Warbanski, Rudman, Hovel, & Matthews, ; Evangelista et al, ), which could be characteristic of each geographical site. Hence, measuring stoichiometric variability of individuals and populations would benefit to infer hypotheses regarding variability in excretion rate.…”
Section: Discussionmentioning
confidence: 99%